Development of Human Papillomavirus (HPV) Vaccines: A Review of Literature and Clinical Update - Chadrakant Sangar, Vikrant; Ghongane, Balasaheb; Mathur, Gaurav (Reviews on Recent Clinical Trials, 2016)
The casual relationship concerning Human papillomaviruses (HPV) and cervical cancer is already established. Therefore, such HPV-associated malignancies might be prevented by prophylactic HPV vaccines. From 2009, two prophylactic HPV L1 Virus-Like Particle vaccines namely, Gardasil® - quadrivalent (Merck) and Cervarix™ - bivalent (GlaxoSmithKline) are widely commercially available. By Aug 2014, 58 countries had introduced HPV vaccination in their national immunization program; this has led to numerous publications on safety and real world effectiveness. We have also seen long-term immunogenicity and efficacy data emerging. Data on cross-protection has also evolved. In clinical trials, it is observed that vaccinating adolescents results in higher immunological response than young adults hence to achieve best HPV vaccine efficacy it is advisable to immunize before the onset of sexual activity. Recently we have seen development of 2 dose vaccine schedule for adolescent, and emerging evidences even point that single dose of HPV vaccines can result in high efficacy, this observation is currently under consideration but if accepted will greatly impact vaccination coverage. In terms of safety, pregnancy registry did not find any unexpected patterns in fetal or maternal outcomes. This review only focuses on the efficacy and safety data of both Food and Drug Administration approved vaccines from clinical phase I to phase IV.
Keywords: Clinical Phases of HPV vaccines